Transformation of dimethyl phthalate esters (DMPEs) by a marine red yeast Rhodotorula mucilaginosa isolated from deep sea sediments of the Atlantic Ocean. (April 2016) - Wang, Jing-Wen; Luo, Zhu-Hua; Xu, Wei; Ding, Jie-Fei; Zheng, Tian-Ling
Abstract: A marine red yeast capable of degrading dimethyl phthalate esters (DMPEs) was isolated from deep-sea sediments of the Atlantic Ocean using enrichment culture technique. The yeast was identified as Rhodotorula mucilaginosa Mar-Y3 based on internal transcribed spacer (ITS) gene sequence analysis. The biochemical degradation pathways of three DMPE isomers, namely dimethyl phthalate (DMP), dimethyl isophthalate (DMI), and dimethyl terephthalate (DMT), were investigated using this yeast. The yeast cannot completely mineralize DMPEs, but can transform them to respective phthalate monoester or phthalic acid. R. mucilaginosa Mar-Y3 also degraded different DMPE isomers through varied metabolism pathways and biodegradation rates. The yeast performed one-step ester hydrolysis with a relatively low degradation rate to transform DMP and DMI to the respective monoester; however, monomethyl phthalate (MMP) and monomethyl isophthalate (MMI) were the dead-end products and further metabolism did not proceed. The yeast carried out sequential ester hydrolysis with a relatively high degradation rate to transform DMT to terephthalic acid (TA) via monomethyl terephthalate (MMT), but TA was resistant to further metabolism. These results suggested that phthalate esterases produced by the deep-sea yeast R. mucilaginosa Mar-Y3 had a very high substrate specificity for different DMPE isomers, and that the degradation of DMPEs by this yeast involved distinct esterases responsible for the hydrolysis of two identical carboxylic ester bonds. Highlights: A red yeast Rhodotorula mucilaginosa Mar-Y3 capable of degrading dimethyl phthalate esters (DMPEs) was isolated from deep sea sediment. The yeast carried out different biochemical pathways to degrade different isomers of DMPEs. The findings suggest that phthalate esterases produced by deep sea yeast R. mucilaginosa Mar-Y3 are highly substrate-specific.